Lived Poverty and the Fate of African Democracies - Edson Ntodwa; Boniface Dulani; Mwayi Masumbu (African Journal of Political Science)
In comparative politics, economic development is a requisite to democracy (Lipset, 1959).   Democracy is deemed to fail in less developed countries as poverty has proven to be detrimental to democratic performance. This study offers a perspective on the effects of poverty on the fate of democracy in Africa. Models are estimated for the Poverty-Democracy linkages using variables derived from merged Afrobarometer survey data (2002-2018). The results indicate that poverty in Africa has a mixed effect on democracy more generally. In particular, the analysis indicates that the experience of poverty, which we have termed ‘lived poverty’, has a negative effect on demand and supply of democracy as well as on a number of attributes of political participation. The fact that the poor demand democracy less than the well-to-do while at the same time perceiving limited supply of democracy, in our view explains why more African regimes are consolidating as hybrid regimes instead of moving towards democratic consolidation